VD_FINDINFO Pron / 2010 / 113 vom 29. Oktober 2010 - VD Tribunal cantonal (2010)
PARTAGESENS GÉNÉRAL, ENCHÈRES, SURSIS AUX ENCHÈRES, VENTE AUX ENCHÈRES FORCÉES | 651 al. 2 CC, 305 al. 2 CPC, 575 CPC, 595 al. 1 CPC, 595 CPC